1988
DOI: 10.1128/jcm.26.4.743-746.1988
|View full text |Cite
|
Sign up to set email alerts
|

Quality of powdered substitutes for breast milk with regard to members of the family Enterobacteriaceae

Abstract: Members of the family Enterobacteriaceae were cultured from 52.5% of 141 milk substitute infant formulas which were obtained in 35 countries. The concentration did not exceed a level of 1 CFU/g in any product. The species which were isolated most frequently were Enterobacter agglomerans, Enterobacter cloacae, Enterobacter sakazakii, and Klebsiella pneumoniae. If infections due to these organisms occur, it can be useful to include a check of the hygienic precautions which are taken during the preparation and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
102
4
9

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(117 citation statements)
references
References 18 publications
2
102
4
9
Order By: Relevance
“…The occurrence of cronobacters in the studies of infant milk formulae has declined in the last two decades from 14AE2% (Muytjens et al 1988) to c. 1-2% (Iversen and Forsythe 2004;Shaker et al 2007;Chap et al 2009;O'Brien et al 2009. The absence of Cronobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of cronobacters in the studies of infant milk formulae has declined in the last two decades from 14AE2% (Muytjens et al 1988) to c. 1-2% (Iversen and Forsythe 2004;Shaker et al 2007;Chap et al 2009;O'Brien et al 2009. The absence of Cronobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…We described a cluster of 12 neonates with NEC treated at our NICU in June-July 1998. E. sakazakii, a rare pathogen known to cause severe neonatal sepsis and meningitis (1, 2, 4, 12-14, 16, 19, 22, 25, 27-28, 30) and to contaminate powdered milk formula (21), was isolated from 6 of the 12 neonates. After a review of feeding procedures, a significant association was found between the development of NEC, the consumption of a brand of powdered milk formula, and the isolation of E. sakazakii in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…the patients. On the other hand Muytjens et al examined a total of 141 different powdered formulas obtained in 35 countries for the presence of members of the Enterobacteriaceae (21). Members of the genus Enterobacter were most frequently isolated: E. agglomerans was cultured from 35 formulas (25%), E. cloacae was cultured from 30 formulas (21%), and E. sakazakii was cultured from 20 formulas (14%) of the 141 formulas examined.…”
Section: Fig 2 Dendrogram Of the Ap-pcr Profiles As Analyzed Withmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the FDA requires that no viable Ent. sakazakii cell must be detected in 333 g of PIF by culture method, whereas contaminations of PIF with 0AE36)66 CFU per 100 g PIF have been reported (Muytjens et al 1988). Therefore, the development of a rapid and highly sensitive detection technique that can substitute for the reference culture method is a pressing matter with regard to clinical and food hygiene tests.…”
mentioning
confidence: 99%